Economic Evaluation of Nitrogen Fertilization Levels in Beef Cattle Production: Implications for Sustainable Tropical Pasture Management - Souza, William Luiz de [UNESP]; Romanzini, Eliéder Prates; Delevatti, Lutti Maneck [UNESP]; Leite, Rhaony Gonçalves [UNESP]; Bernardes, Priscila Arrigucci; Cardoso, Abmael da Silva; Reis, Ricardo Andrade [UNESP]; Malheiros, Euclides Braga [UNESP] (MDPI, 2023)
Understanding economic scenarios is crucial in all production chains. Tropical pastures are Brazil’s primary food source for beef cattle production, and current pasture management is not ideal due to land degradation. An economic evaluation assists farmers with improving pasture management using novel techniques, such as nitrogen (N) fertilization, which is straightforward and practical. The economic effects of different N fertilizer levels in beef cattle production were evaluated. This study was conducted over three years (2014/2015, 2015/2016, and 2016/2017) using four concentrations of urea fertilizer (0, 90, 180, and 270 kg N/ha). A principal component analysis and sensitivity analysis were performed using financial data. A financial pattern was observed, with increases in some variables, such as cost-effective operating and cost-total operating from those measuring costs and gross revenue, operating profit, and net income from those estimating revenues. Treatment with 180 kg N/ha fertilizer resulted in increased profitability, payback, internal rate of return, and net present value (at 6% and 12% tax) of 17.76%, 2.79 years, 35.79%, and USD 5926.03 and USD 1854.35, respectively. For this study, the main costs associated with profitability were supplementation, animal purchases, and sale prices. The best treatment to achieve excellent grazing pressure in tropical areas with oxisol is 180 kg/ha per year.
Keywords: cost-total operating; nitrogen fertilization; pasture management; principal component analysis; sustainable farming